Ultrafast Growth of Large 2D Silver Nanosheets by Highly Ordered Biological Template at Air/Gel Interface. Issue 10 (2nd March 2018) - Jang, Hyung‐Seok; Seong, Baekhoon; Zang, Xining; Lee, Hyungdong; Bae, Jin Woo; Cho, Dae‐Hyun; Kao, Emmeline; Yang, Chen; Kang, Giho; Liu, Yumeng; Park, Hyun Sung; Byun, Doyoung; et al.
Abstract: The growth of large and high‐quality 2D nanomaterials is challenging due to the formation of defects from dislocations, disinclinations, and symmetry‐breaking instabilities. In this study it is demonstrated that biological template can be utilized to align the molecular orientation for large grain size in the synthesis of the high‐quality 2D silver nanostructure. The solvent assisted multilayering phenomenon of hydrogel forms biological template at the air/gel interface and supports the silver salts to grow laterally and largely in a 2D manner between the scaffold layers with a nominal thickness of 4.4 ± 0.3 nm. This solution‐based deposition mechanism is demonstrated based on droplet, spin‐coating, and electrohydrodynamic jet printing schemes for robust and flexible conductive thin films or patterns. Abstract : Biological template can be utilized to align the molecular orientation for large grain size in the synthesis of the high‐quality 2D silver nanostructure. The multilayering phenomenon of hydrogel forms biological template at the air/gel interface and supports the silver salts to grow laterally and largely in a 2D manner between the scaffold layers with a nominal thickness of 4.4 ± 0.3 nm.